Interplay of gut microbiota, glucagon-like peptide receptor agonists, and nutrition: new frontiers in metabolic dysfunction-associated steatotic liver disease therapy - Güney Coşkun, Merve; Başaranoğlu, Metin (My University, 2024)
The gut-liver axis plays a crucial role in the development and progression of metabolic dysfunction-associated steatotic liver disease (MASLD). Key metabolites, including lipopolysaccharides, short-chain fatty acids (SCFAs), bile acids, and beneficial gut bacteria such as Bifidobacterium and Lactobacillus, are pivotal in this process. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) show promise in managing MASLD by promoting weight loss, enhancing insulin secretion, and improving liver health. They restore gut-liver axis functionality, and their effects are amplified through dietary modifications and gut microbiome-targeted therapies. Emerging research highlights the interplay between GLP-1 RAs and gut microbiota, indicating that the gut microbiome significantly influences therapeutic outcomes. Metabolites produced by gut bacteria, can stimulate glucagon-like peptide-1 (GLP-1) secretion, further improving metabolic health. Integrating dietary interventions with GLP-1 RA treatment may enhance liver health by modulating the gut microbiota-SCFAs-GLP-1 pathway. Future research is needed to understand personalized effects, with prebiotics and probiotics offering treatment avenues for MASLD.
Keywords: Diet Intervention; Glucagon-Like Peptide-1 Receptor Agonists; Gut Microbiome; Gut-Liver Axis; Metabolic Dysfunction-Associated Steatotic Liver Disease